Maternal Employment and Nutritional Status of Preschool Children - Mini P Jose (Department of Home Science, College of Horticulture, 1998)
A study on "Maternal Employment and Nutritional Status of Preschool Children" was carried out among 120 children in the age group of 4 to 5 years. They were selected on the basis of maternal employment equally and randomly from the three groups i.e., casual labourers (CL), employed mothers (EM) and unemployed mothers (HW). The results of the study indicated that Hindus were the majority in all the three groups. Majority of the parents were literate with family income ranging between Rs.2000 and Rs.8000. Most of the families in the EM and HW groups had a joint existence. Majority of the families did not own land or livestock but owned a kitchen garden. Monthly expenditure pattern revealed that the greatest amount was spent on foods in which cereals had the major share. Various contagious diseases were more prevalent in the CL community. Social participation was low in all the three groups with highest participation in EM group. Frequency of use of different foodstuffs revealed that cereals, pulses, other vegetables, milk and milk products, fats and oils, sugar and spices and condiments were the most frequently used items in all the three groups. Advance meal planning was highest in the EM group. In majority of the families there was equality in food distribution. Majority of mothers worked between 8 to 10 hours a day for more than 21 days per month. Financial constraint was the major reason for opting to work Most of the working mothers were satisfied with their jobs.